Clinicopathological Analysis and Surgical Outcome of Eyelid Malignancies: A Study of 332 Cases - Syeed Mehbub Ul Kadir; Mukti Rani Mitra; Riffat Rashid; Murtuza Nuruddin; Md. Kamrul Hassan Khan; Golam Haider; Mst. Sayedatun Nessa (Journal of Skin Cancer)
Background. Eyelid tumours are common in our ophthalmic practice. Malignancy cases account only for one-fourth of all eyelid tumours. The most aggressive eyelid malignancy is sebaceous gland carcinoma, but its occurrences are rare in western countries. We found sebaceous gland carcinoma is as common as basal cell carcinoma in our clinical practices. Hence, it is essential to build awareness about the more aggressive eyelid malignancies to reduce morbidity and mortality. Aim. To assess the relative frequency of eyelid malignancies in the Bangladesh population, state their clinical features and outcome of management strategies and build awareness about the more aggressive eyelid malignancies to reduce morbidity and mortality. Methods. This was a retrospective case series study of 332 patients in Bangladesh. This study analyzed all the recorded data of the histologically proven primary eyelid malignancies and followed them up for at least six months from 2014 to 2019 (6 years). All patients were managed by surgical excision with tumor-free margins verified on histopathology, either the frozen section or excision biopsy with 2–3 mm microscopic view of normal tissue followed by eyelid reconstruction. Computer-based statistical software SPSS was used for the analysis, and an appropriate test of significance (chi-square) was used for the statistical analysis. Results. Sebaceous gland carcinoma (SGC) was the highest in occurrence, at 42%, followed by 38% basal cell carcinoma (BCC), 18% squamous cell carcinoma (SqCC), and 02% malignant melanoma (MM). The mean age at presentation of SGC, BCC, SqCC, and MM were 57.41 years, 62.56 years, 64.73 years, and 59.28 years, respectively. Female (59%) was slightly more preponderance over the male (41%) for SGC than other malignancies. Pigmentation was associated with malignant melanoma (100%) and BCC (81%). Statistically, a significant difference was found between eyelid malignancies, including location, size, pigmentation, recurrence, and invasiveness. The recurrence rate was low lower in the patients who underwent frozen section biopsy (3%) for margin clearance than those who underwent excision biopsy (21.5%) in the follow-up time. Conjunctival map biopsy (8%) was performed as an essential tool for excluding the pagetoid spread of SGC. A new reconstruction method named triangular-shaped musculocutaneous tail flap was performed in 33 (11%) patients to reconstruct the moderate eyelid defect following local resection. Conclusion. Sebaceous gland carcinoma (SGC) was the highest occurrence found to be the highest occurrence among all eyelid malignancies in Bangladesh. SGC is more aggressive and the recurrence rate was higher than BCC and SqCC.